Mature Imaging-Based Outcomes Supporting Local Control for Complex Reirradiation Salvage Spine Stereotactic Body Radiotherapy. Issue 4 (6th May 2020) - Detsky, Jay S; Nguyen, Timothy K; Lee, Young; Atenafu, Eshetu; Maralani, Pejman; Husain, Zain; Tseng, Chia-Lin; Myrehaug, Sten; Soliman, Hany; Sahgal, Arjun
Abstract: BACKGROUND: Upon progression after upfront radiotherapy to spinal metastases, low-dose re-irradiation conventional external beam radiation (cEBRT) provides limited clinical benefit. Spine stereotactic body radiotherapy (SBRT) allows for dose escalation in the salvage setting with the potential for improved local control. OBJECTIVE: To report mature clinical and imaging-based outcomes for salvage SBRT. METHODS: A retrospective review was undertaken of consecutive patients with spinal metastases treated with re-irradiation spine SBRT having failed either cEBRT (n = 60 with 1 prior course and n = 17 with 2 or more prior cEBRT courses), or prior SBRT (n = 6) to the same spinal segment. The primary outcome was local failure (LF), and secondary outcomes included overall survival (OS) and the rate of vertebral compression fracture (VCF). RESULTS: A total of 43 patients with 83 spinal segments treated with salvage SBRT were reviewed. The crude risk of LF was 18%, and actuarial LF rates at 6, 12, and 24 mo were 7%, 14%, and 19%, respectively. The presence of extensive paraspinal disease (hazard ratio [HR] = 7.1, 95% CI 1.5-34) significantly predicted for LF. The median OS was 13.2 (95% CI 6.1-16.3) mo, and the presence of neurological deficits (HR = 4.7, 95% CI 1.8-12.1) and brain metastases (HR = 2.6, 95% CI 1.1-6.3) were significant prognostic factors. The crude risk of VCF was 4%, and radiation myelopathy was not observed. CONCLUSION: These data support the safety and efficacy of spinal re-irradiation with SBRT including patients with prior SBRT and multiple courses of prior cEBRT.